Library education for secondary school students in Jeddah | التربية المكتبية لطالبات المرحلة الثانوية بمدينة جدة - Banajah | باناجه, Iman Abdel Aziz | إيمان عبد العزيز (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
This study aims to identify the reality of library education in girls’ secondary schools in Jeddah. In her study, the researcher relied on the scientific analysis of three textbooks that include: On the prescribed curriculum for “library subject” for female students in those schools, in terms of form and substantive content; It also polled the opinion of 120 female students, representing 20% of the total number of first-level female students at King Abdulaziz University in Jeddah, who had completed studying these three books in the secondary stage, in addition to polling the opinion of 25 female teachers who teach “library subject” in those schools, representing 18% of the total. There are 140 female teachers in the subject | تهدف هذه الدراسة التعرف إلى واقع التربية المكتبية في المدارس الثانوية للبنات بمدينة جدة . ولقد اعتمدت الباحثة في دراستهـــا علـــى التحليل العلمـــي لثلاثة كتب دراسيـــة تشتمل على المنهج الدراسي المقرر " لمادة المكتبة " لطالبات تلك المدارس، من حيث الشكل والمحتوى الموضوعي ؛ كما قامت باستطلاع رأي 120 طالبة بنسبة 20% من مجموع عدد طالبات المستوى الأول بجامعة الملك عبدالعزيز بجدة واللاتي أتممن دراسة هذه الكتب الثلاثة في المرحلة الثانوية، بالإضافة إلى استطلاع رأي 25 معلمة ممن يقمن بتدريس " مادة المكتبة " في تلك المدارس بنسبة 18% من مجموع معلمات المادة فيها والبالغ عددهن 140 معلمة